The analysis of roof fall risk assessment methods in underground workings - Domrachev, A.N.; Govorukhin, Yu.M.; Krivolapov, V.G.; Paleev, D.Yu. (Publishing House of the KarSU named after E.A.Buketov, 2016)
This article proves the relevance of the roof fall risk assessment. It bases both in terms of predicting the possibility of their reuse and keeping the coal pillars stability, and the risk of the origin of closed unventilated areas, which unavoidably accumulate explosive gas-air mixtures. The most widespread foreign methods of roof fall risk assessment in mine workings have been considered. They include an algorithm for calculating the index of the level of roof fall risk (RFRI) and the method of assessing the stability of the pillars of the New South Wales University (UNSW). The possibility of using of the roof fall risk assessment methods to improve the efficiency and safety of mining operations in South Kuzbass mines has been tested on a specific example.
Keywords: a probability of risk fall; factor of probability; weight factor; roof support; expert estimation; category of risk